An Easy Route to Red Emitting Homoleptic IrIII Complex for Highly Efficient Solution‐Processed Phosphorescent Organic Light‐Emitting Diodes. Issue 27 (24th June 2014) - Giridhar, Thota; Han, Tae‐Hee; Cho, Woosum; Saravanan, Chinnusamy; Lee, Tae‐Woo; Jin, Sung‐Ho
Abstract A thiophene‐phenylquinoline‐based homoleptic IrIII complex, [Ir(Th‐PQ)3], has been synthesised by a simple route and utilised as a dopant in solution‐processed phosphorescent organic light‐emitting diodes (PhOLEDs). It shows the current efficiency of approximately 26 cd A−1 and the external quantum efficiency of about 21 %, which are the highest values reported to date for PhOLEDs prepared by solution‐process.